Are mobile devices playing a part in creating new tourist practices? Les Champs-Elysées: a case study - Marie Delaplace; Leïla Kebir (Via@, 2020)
Mobile devices (smartphones and tablets) have the potential to change tourist practices in a place. They allow tourists to directly book accommodation, activities or restaurants. They can affect access and circulation within a destination, as well as the tourist’s experience. The aim of this paper is to ascertain whether these mobile devices actually change tourist practices in situ. A survey was therefore carried out in May-June 2018 on the Champs-Elysées in Paris. This allowed us to identify the types of people on the Champs-Elysées, their reasons for being there, and how they were using their mobile devices. Drawing on the data relating to respondents who described the purpose of their visit as “tourism”, we shall demonstrate that although they had access to this technology, and over three-quarters had internet connectivity, their usage was ultimately very traditional in that it largely facilitated pre-existing practices in a different way.